Autobiographical event memory and aging: older adults get the gist. Issue 12 (December 2022) - Grilli, Matthew D.; Sheldon, Signy
Abstract : We propose that older adults' ability to retrieve episodic autobiographical events, although often viewed through a lens of decline, reveals much about what is preserved and prioritized in cognitive aging. Central to our proposal is the idea that the so-called gist of an autobiographical event is not only spared with normal aging but also well adapted to serve memory-guided behavior in older age. To support our proposal, we review cognitive and brain evidence indicating an age-related shift toward gist memory. We then discuss why this shift likely arises from more than age-related decline and instead partly reflects a natural, arguably adaptive, outcome of experience, motivation, and mode-of-thinking factors. Our proposal reveals an upside of age-related memory changes and identifies important research questions. Highlights: Cognitive aging is often viewed through the lens of loss of function. Research examining the way older adults remember autobiographical event memories, therefore, has focused on how aging reduces the ability to form and retrieve specific details, with less emphasis on understanding the aspects of event memories that are preserved among older adults. We propose that at the heart of what is preserved in older adults' autobiographical event memories is the selective sparing of the ability to store and retrieve the gist. We discuss why older adults' reliance on gist may be driven by multiple factors beyond cognitive decline, including changes in goals that come with age.